(untitled) (International Journal of Plant Biology, 2020)
Although the effect of salinity on plants is well established, yet evaluating genetic variation in yield-related traits under salinity stress remains useful. This study was conducted to investigate the genetic variation within and between two subgroups of durum wheat in Jordan, i.e., cultivars and landraces, in germination and root architectural traits at three salinity concentrations (50, 100 and 150 mM NaCl). The results indicate that salinity significantly impacted most traits investigated. A multivariate discriminant analysis (DA) revealed large variations ( 85%) between genotypes, with significant ranking in maximum root length, total root length, seminal root length, coleoptile length, germination percentage, and total and seminal root number over the three salinities. Within the cultivar subgroup, salinity significantly influenced the germination percentage and most root traits of durum genotypes, with variable magnitudes depending on NaCl concentration and within-variety intraspecific genetic variation (ANOVAs; P<0.05). However, within the landrace subgroup, only a salinity of 150 mM NaCl significantly affected the studied traits, and the effect of salinity on germination percentage was highly genotype dependent. Additionally, the durum genotypes in the landrace subgroup were more affected by salinity and showed more genetic variation than those in the cultivar subgroup.